Vocal Cord Paresis After Posterior Spinal Fusion to Treat Adolescent Idiopathic Scoliosis: A Case Report. Issue 4 (October 2016) - Rao, Rameshwar R.; Ha, Jennifer; Farley, Frances A.; Koopmann, Charles F.; Caird, Michelle S.
Abstract : Case: A 15-year-old girl with adolescent idiopathic scoliosis with a 50° curve underwent posterior spinal fusion from T3 to T11. After discharge from the hospital, the patient reported dysphonia and dysphagia. Flexible nasendoscopy confirmed left vocal cord paresis. Stretch injury to the recurrent laryngeal nerve from the left T5 pedicle screw or intubation may have caused the vocal cord paresis. The pedicle screw was removed during revision surgery. Postsurgically, the patient demonstrated immediate and ultimately full recovery and no longer had any symptoms. Conclusion: To our knowledge, this is the first case report of vocal cord paresis most likely caused by pedicle screw position after posterior spinal fusion.